Methods for Increasing the Communicative Activity of Future Teachers in An Online Educational Environment (International Journal of Scientific Trends, 2026)
This article examines the theoretical foundations, methodological approaches, and practical methods for increasing the communicative activity of future teachers in an online educational environment. The expansion of digital education requires the educator not only to convey the content of the subject but also to manage communication in a virtual environment, engage students in collaboration, harmonize written and oral speech, and develop reflexive thinking.